Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1097/pas.0b013e3181d96231
|View full text |Cite
|
Sign up to set email alerts
|

Silver In Situ Hybridization (SISH) For Determination of HER2 Gene Status in Breast Carcinoma

Abstract: The importance of HER2 status in breast cancer management has focused attention on the ability of clinical assays to correctly assign HER2 amplification status. There is no consensus as to the best method for assessing HER2 status. Disadvantages of fluorescence in situ hybridization (FISH) testing include longer time required for staining and scoring slides, requirements for specialized training and fluorescence microscopy, and loss of the signal due to quenching of the fluorescent dye. Silver-enhanced in situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
48
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 44 publications
9
48
0
1
Order By: Relevance
“…These results are consistent with previous data available on surgical specimens. [12][13][14]33 In conclusion and based on our results, immunohistochemistry status assessed on cores biopsy is highly concordant with FISH in cores and surgical specimens. Furthermore, CISH and/or SISH even represents a safe alternative method to determine HER2 status on these cores biopsies to confirm any ambiguous immunohistochemistry results (2 þ ) or to perform HER2 status screening, if ISH is used as first-line screening method.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…These results are consistent with previous data available on surgical specimens. [12][13][14]33 In conclusion and based on our results, immunohistochemistry status assessed on cores biopsy is highly concordant with FISH in cores and surgical specimens. Furthermore, CISH and/or SISH even represents a safe alternative method to determine HER2 status on these cores biopsies to confirm any ambiguous immunohistochemistry results (2 þ ) or to perform HER2 status screening, if ISH is used as first-line screening method.…”
Section: Discussionsupporting
confidence: 71%
“…[8][9][10][11] SISH was implemented more recently and three studies reported a 97, 96 and 87% concordance between SISH and FISH results on excision samples [12][13][14] taking into account that discordant cases could be partly explained by intratumor heterogeneity of amplification. One study showed an 89% concordance of SISH results between surgical specimens and core-needle biopsies but the number of studied cases was limited (n ¼ 56).…”
mentioning
confidence: 99%
“…Until now, some studies have been performed to compare FISH and SISH methods with a correlation ratio of 89-98% (Dietel et al, 2007;Carbone et al, 2008;Papouchado et al, 2010;Ying et al, 2010;Park et al, 2011;Lee et al, 2012;Tvrdík et al, 2012). A correlation ratio of 92.3% was found in this study between FISH and SISH.…”
Section: Discussionmentioning
confidence: 51%
“…Pre-analytic factors affect the test results less than immunohistochemistry. Nevertheless, the FISH technique is more expensive, it necessitates special equipment and educated personnel, its application process lasts longer, and a fluorescent microscope is required for the evaluation of the test (Francis et al, 2009;Papouchado et al, 2010;Ying et al, 2010;Arnould et al, 2012;Schiavon et al, 2012). The SISH method, which can be an alternative to the FISH technique, is comprised of a multimer technology, combined with enzyme metallography, which allows for the identification of the HER2 oncogene amplification with silver marking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation